Video Promosi Pada Fave Hotel LTC Glodok Jakarta Sebagai Penunjang Informasi - Nurlaila Suci Rahayu Rais; Eduard Hotman Purba; Siti Mutia Isnaini (UNIVERSITAS RAHARJA, 2018)
The development of today's technology is very advanced and very important to today's society. This proves that more and more information can be obtained through print media or electronic media and for nowadays social media can also get information. Currently Fave Hotel LTC Glodok Jakarta, the promotional media is provided through print media such as brochures, flyers and other print media or through social media such as instagram to provide information about the hotel. In order for the promotion media to be well communicated and accepted by the public through the promotion video will be easier to understand and the promotion video is presented with an interesting look by using software such as Adobe Premiere and Adobe After Effect for the editing of this promotional video. Adobe Premiere and Adobe After Effect to give the effect more attractive and easier to unify the video into one to become the desired video. The method used is data collecting observation, problem analysis, production concept method, design analysis method and mavib production concept (KPM) which include preproduction, production and postproduction. With this promotional video media it is able to make Fave Hotel LTC Glodok Jakarta easier to provide information to the public about the hotel. Promotional videos made with interesting concepts such as video bloggers (VLOG) for today are indeed in the interest of the wider community. With the aim of this research intends to make promoting media through video that is hopefully helpful and helpful to Fave hotel LTC Glodok Jakarta it is easier to provide information to the public about the hotel especially for lodging service users. The contents of this promo video include facilities available and the nearest destination tour of Fave Hotel LTC Glodok Jakarta.